Application Value of the CT Scan 3D Reconstruction Technique in Maxillofacial Fracture Patients. (7th July 2022) - Kang, Jie; Jiang, Lijie
Abstract : Purpose The aim of the study was to explore the application value of computerized tomography (CT) scan 3D reconstruction technology in maxillofacial fracture patients. Methods A total of 80 maxillofacial fracture patients who underwent surgical treatment in Shijiazhuang People's Hospital from January 2019 to January 2020 were enrolled. All of them received 128-slice spiral CT scans before surgery, and the images were subjected to multiplanar reconstruction (MRP) and volume reconstruction (VR). Results A total of 181 fractures were found in 80 patients with maxillofacial fractures. The detection rates of axial CT, MRP, and VR were 77.90% (141/181), 93.92% (170/181), and 97.79% (177/181), respectively. The detection rates of the four inspection methods were statistically different. Taking the findings of surgical anatomy as the gold standard, the sensitivity of MRP and VR for the diagnosis of maxillofacial fractures was 90.06% (163/170) and 95.56% (174/177), with no significant difference. Conclusion CT scan 3D reconstruction technology has a high application value in the clinical diagnosis and treatment of maxillofacial fracture patients.